The Business Management of Local Government Unit Operated Slaughterhouses in Cities of Region V, Philippines - Iglesia, Maria Joy C. (The Indonesian Institute of Science and Technology Research, 2024)
This study assessed the operations management of Local Government Unit (LGU) slaughterhouses in the Bicol Region. It specifically examined: compliance with standards in human resources, marketing, finance, and operations; priority management areas for intervention; and recommendations for improvement. Data were gathered through surveys, interviews, and observations, with 161 slaughterhouse operators as respondents, and analyzed using descriptive statistics. Findings indicate that most LGU slaughterhouses do not fully comply with government standards. Slaughterhouses in Iriga, Legazpi, and Tabaco partially meet standards but lack complete facilities, including drainage, lagoons, sterilizers, and meat handling equipment. Cleaning is insufficient, leaving floors unhygienic, while personnel evaluation and training are not conducted. Marketing services are limited, with no “bantay karne” (meat watcher) programs or public awareness campaigns. Revenue and service pricing are guided by local ordinances. Conversely, slaughterhouses in Ligao, Naga, and Sorsogon comply with standards due to good manufacturing practices (GMP), sanitation programs, complete facilities, and trained personnel with performance evaluations. Priority areas needing improvement include human resource management, marketing services, financial procedures, and facility maintenance. The study recommends implementing personnel evaluations, training programs for “bantay karne,” improved sanitation practices, and a quality management monitoring checklist to identify and address gaps. Annual monitoring is proposed to ensure consistent improvements in LGU-operated slaughterhouses.